Factors influencing information communication technology utilization among student teachers of Malaysian Research Universities - Mirzajani, Hassan (2017)
The purpose of this correlational study is to investigate the extent of ICT utilization and its relationship with ICT attributes, perceived usefulness, perceived ease of use, attitudes toward ICT use, and facilitating conditions among student teachers in Malaysian Research Universities. It also sought to determine the availability of the conditions that facilitate ICT utilization among student teachers. In addition, the study determined whether perceived usefulness, perceived ease of use, attitudes toward the use of ICT, ICT attributes and facilitating conditions are predictors of ICT utilization among student teachers.